Excess of Mortality in Adults and Elderly and Circulation of Subtypes of Influenza Virus in Southern Brazil - Freitas, André Ricardo Ribas; Donalisio, Maria Rita (Frontiers in Immunology, 2018)
Purpose: In the elderly population, the influenza infection and its clinical complications are important causes of hospitalization and death, particularly in longer-lived age. The objective of this study is to analyze the impact of influenza virus circulation on mortality in the elderly and adults, in years with different predominant virus strains. Methods: We performed a time trend study to evaluated excess of mortality for pneumonia and influenza, respiratory disease, and all-causes in southern region of Brazil, from 2002 to 2015. After considering other models, we opted for , using a Serfling regression model. Excess of death rates per 100,000 inhabitants were analyzed in specific age groups (24-59, 60-69, 70-79, ≥ 80 years) and by year of occurrence. Mortality information were taken from Brazilian Mortality Information System and etiological data were accessed in Sentinel Virological Surveillance data base, getting the weekly positivity of the immunofluorescence tests for influenza A (H1N1, H3N2), and B. Results: In southern Brazil, there is an evident seasonal pattern of all death outcomes among different age groups in the dry and cold season (April – September). The highest excess mortality rates occurs among older, particularly in years of circulation of influenza AH3N2, especially among people ≥ 80 years, in 2003 and 2007 – years of great severity of influenza activity. After 2009, with the introduction of the pandemic influenza AH1N1, we observed a lower impact on the mortality of the elderly compared to < 60 years. Discussion: A cross reactivity antibody response from past exposure probably provided protection against disease in the elderly. Despite not controlling for comorbidities, climate, and vaccination, fFor the > 70 years, ratio of respiratory diseases excess mortality rates between AH1N1 (2009) and severe year of H3N2 (2007) shows protection in the pandemic year and great vulnerability during AH3N2 virus predominance. Conclusion: The reduced immune response to infection, and to vaccination, and presence of comorbidities recommend a special attention to this age group in Brazil. Besides medical assistance, the timeliness of vaccine campaigns, its composition and etiological surveillance of respiratory diseases are some of the preventive and public health measures.